QT Interval Derived Measurements in Patients with Cardiac Syndrome X Compared to Coronary Artery Disease - Lutfi, Mohamed F. (Frontiers in Physiology, 2016)
Previous studies assessing effect of ischemia on ventricular repolarization are mostly directed towards patients with coronary artery disease (CAD); however, similar reports on cardiac syndrome X (CSX) are scarce. Whether microvascular dysfunction of CSX and ischemia induced by CAD produce comparable effect on ventricular repolarization is unclear and deserve further studies. In the present study, ECG measures of ventricular repolarization were compared between CAD and CSX patients (40 subjects in each group). Following evaluation of sociodemographic characteristics, medical and past medical history, a resting ECG was used to assess measurements of ventricular repolarization in each patient, namely, QT interval (QT), corrected QT interval (QTc), QT dispersion (QTd), corrected QT dispersion (QTcd), adjacent QT dispersion (AdQTd), QT dispersion ratio (QTdR), JT dispersion (JTd) and Corrected JT dispersion (JTcd). Results showed comparable QT intervals and QTd in CAD and CSX patients even after adjustment for the possible variations in gender, age and body mass index of the studied groups. Although JTd was increased in CSX subjects (26.6±7.2 ms) compared with CAD patients (22.7±6.5 ms, p = 0.019), statistical significance disappeared after correcting JT for variations in heart rate. QT and QTc were significantly below 440 ms in CAD as well as CSX patients (p < 0.001). In contrast, maximum QTd, maximum QTcd and AdQTd of CAD and CSX patients were significantly above 440 ms (p < 0.001). The means of JTd and JTcd were significantly above 22 ms and 24 ms respectively (p < 0.001, p = 0.001) in CSX but not CAD patients (p = 0.529, p = 0.281). The present findings clearly demonstrate comparable measures of ventricular repolarization in CAD and CSX patients and consequently the risk of cardiac events.